Who is cheating? The role of attendants, risk aversion, and affluence - Olaf Hübler; Lukas Menkhoff; Ulrich Schmidt (Deutsches Institut für Wirtschaftsforschung (DIW), 2018)
This research integrates a standard "cheating" experiment into a broad household survey and finds relationships between individual characteristics and cheating behavior. We allow for attendance of others at the cheating experiment, addressing the "reputation to be seen as honest," finding there is indeed less cheating with attendants. Regarding the preference for "honesty," we find two related attitudes: stronger risk aversion increases the costs of cheating, i.e. behaving against the norm, while affluence makes cheating costly, as it allows behaving honestly. The underlying experiment in rural Thailand reproduces stylized facts of the cheating literature.
Keywords: D01; D81; D82; 330; cheating; individual characteristics; risk attitude